2014
DOI: 10.1111/adj.12218
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and microbial adherence ability of modified polymethylmethacrylate by fluoridated glass fillers

Abstract: Background: The current study objectives were to evaluate the influence of fluoridated glass fillers loading on the surface roughness, wettability, and adherence of candida and bacteria with and without saliva presence to a polymethylmethacrylate (PMMA) denture base material surface. Methods: Four concentrations of fluoridated glass fillers were added to PMMA: 1%, 2.5%, 5% and 10% by weight prepolymerization and 0% was the control. Discs of each concentration were fabricated (n = 5 for each variable). Surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
0
28
0
5
Order By: Relevance
“…To reinforce the properties of PMMA materials, a variety of filler particles have been investigated, including ceramics and metals ( Table 7 ). It is obvious from these studies that the addition of particles resulted in no biocompatibility issues and improved various properties of the PMMA, including the mechanical properties [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], thermal conductivity [ 23 , 24 , 31 , 254 , 255 ], dimensional stability [ 256 ], and antimicrobial activity [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 ], and also reduced the solubility and water sorption [ 267 , 268 ]. The beneficial outcomes resulting from the use of nanoparticles are achieved due to their characteristic features, such as their high surface area and better distribution [ 34 , 269 ].…”
Section: Modifications Of Pmmamentioning
confidence: 99%
See 1 more Smart Citation
“…To reinforce the properties of PMMA materials, a variety of filler particles have been investigated, including ceramics and metals ( Table 7 ). It is obvious from these studies that the addition of particles resulted in no biocompatibility issues and improved various properties of the PMMA, including the mechanical properties [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], thermal conductivity [ 23 , 24 , 31 , 254 , 255 ], dimensional stability [ 256 ], and antimicrobial activity [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 ], and also reduced the solubility and water sorption [ 267 , 268 ]. The beneficial outcomes resulting from the use of nanoparticles are achieved due to their characteristic features, such as their high surface area and better distribution [ 34 , 269 ].…”
Section: Modifications Of Pmmamentioning
confidence: 99%
“…To impart antimicrobial properties on the materials, various modifications have been reported, such as the addition of antimicrobial polymers, inorganic nanoparticles, or medicaments, as well as surface functionalization, demonstrating promising outcomes against various oral microorganisms [ 290 ]. Several studies have reported the inhibition of microbial adhesion and growth on PMMA surfaces containing fluoride glass fillers [ 264 , 265 ], fluorapatite, or apatite-coated TiO 2 [ 262 , 263 ]. The availability of fluoride in the oral cavity results in the enhancement of antibacterial activity against the oral microbiomes [ 291 ].…”
Section: Modifications Of Pmmamentioning
confidence: 99%
“…Microbial adhesion significantly decreased with saliva coating [60]. Al Bakri et al also emphasized on there may many factors on the attachment of microorganisms to PMMA surfaces such as microorganism surface charge, surface roughness, surface morphology, surface topology, surface free energy and presence and non presence of saliva coating [60]. Table 1 shows numerical data of Candida attachment extracted from the literature.…”
Section: Candi̇da Adezyonu üZeri̇ne Etki̇si̇)mentioning
confidence: 99%
“…The advances in polymer technology have produced novel polymers such as high-impact polymers and fiber-reinforced polymers with improved impact strength and fatigue resistance. The polymer modifications are achieved either by incorporating additives such as rubber,[10] styrene-butadiene,[11] Al 2 O 3 ,[12] and β-AgVO 3 [13] or by adding inorganic fillers such as metallic oxides,[14] fluorinated glass fillers,[15] hydroxyapatite whiskers,[16] zirconia,[17] and organic fibers[18] of carbon/graphite, aramid, ultra-high modulus polyethylene, nylon, and jute. Reviews of studies regarding the polymeric modifications are available in the dental literature.…”
Section: Introductionmentioning
confidence: 99%